Single-pot, solid-phase-enhanced sample preparation for proteomics experiments - Hughes, Christopher; Müller, Torsten; Krijgsveld, Jeroen (Nature protocols, 2019)
This protocol describes a single-pot, solid-phase-enhanced sample-preparation (SP3) method for rapid, robust, and efficient processing of protein samples for proteomic analysis.
Published: 21 November 2018
Gesehen am 05.06.2019